Reposicionamento de medicamentos em doenças infecciosas e avaliação da atividade biológica de inibidores da bomba de prótons e benzodiazepínicos - Rosa, Taciéli Fagundes da (2022)
A pathological condition with a high level of severity, caused by drug resistance, is one of the major public health problems worldwide and has worrying consequences. This scenario becomes more complex when we mention the infections caused by the pathogens ESKAPE - Enterococcus faecium, Staphylococcus aureus, Klebsiella pneumoniae, Acinetobacter baumannii, Pseudomonas aeruginosa and Enterobacter spp. - (because they are microorganisms with high multiresistance and virulence). Thus, repositioning has been a trending topic in the literature and consists of finding new uses for drugs approved for clinical use. In this sense, the present study aimed, in the published articles, to present to the scientific community the current research on treatment alternatives for infections caused by ESKAPE pathogens and perspectives on the anti-infective activities of proton pump inhibitors (PPIs). In the manuscripts, the biological activities of the benzodiazepines clonazepam and diazepam and PPIs omeprazole and esomeprazole as candidate drugs for redirection were verified. Scientific database searches were carried out on treatment alternatives for ESKAPE pathogens and anti-infective activities of PPIs. In addition, the in vitro antibacterial activities of clonazepam, diazepam, omeprazole and esomeprazole against American Type Culture Collection (ATCC) standard bacterial strains and clinical isolates of ESKAPE pathogens were analyzed, determining the minimum inhibitory concentration (MIC), minimum bactericidal concentration (MBC), its interactions with the standard antibacterial ciprofloxacin by the checkerboard method and determination of the fractional inhibitory concentration index (FICI). For clonazepam and diazepam, the clinical impact of the use of these drugs in repositioning was analyzed, and for omeprazole and esomeprazole, the ability to cleave plasmid DNA was verified, and molecules capable of cleavage can act as antibacterials. In the treatment alternatives for infections caused by ESKAPE pathogens, drugs from the pharmacological classes of antineoplastic, anti-inflammatory, antidepressant and antialcoholic have been reported. In the study covering the anti-infective activities of PPIs, activities of these drugs against 17 infectious agents were described, some of them Pseudomonas aeruginosa, Mycobacterium tuberculosis, Enterococcus faecalis, Staphylococcus aureus, Candida albicans and SARS-CoV-2. In antibacterial activity assays, the combination of clonazepam and diazepam with ciprofloxacin was synergistic against 10 strains and five strains of ESKAPE pathogens (FICI<0.5), respectively. The combination of omeprazole and esomeprazole with ciprofloxacin was synergistic against two strains and three strains of ESKAPE pathogens (FICI<0.5), respectively. In the plasmid DNA cleavage assay, it was evidenced that omeprazole and esomeprazole were able to cleave plasmid DNA under defined conditions of pH, temperature and reaction times, being hydrolytic the main mechanism involved (omeprazole 37ºC pH 7.4 and pH 8.0; esomeprazole 37°C pH 7.4 and pH 8.0 - 50°C pH 8.0). We conclude that drug redirection is a promising approach against bacterial infections caused by bacteria with high multi-resistance to antibacterials. Furthermore, we encourage the development of more in vitro and in vivo studies involving the antibacterial activity of benzodiazepines and proton pump inhibitors, in order to be implemented as adjuvants in cases of serious infections caused by pathogens such as ESKAPE.